Significant Increases in Wet Nighttime and Daytime–Nighttime Compound Heat Waves in China from 1961 to 2020 - Xi Chen (Atmosphere, 2023)
Heat waves (HWs) with high humidity are dangerous to human health. However, existing studies on different types of HWs considering the effect of humidity are still limited. This study defines three types of wet summer HWs (that is, wet independent daytime and nighttime HWs and wet daytime-nighttime compound HWs) and investigates their spatial-temporal changes across China during 1961–2020. Results show significant upward trends of wet nighttime and compound HWs in terms of frequency, occurring days, duration, intensity and spatial extent, while changes for wet daytime HWs are weak and insignificant in nearly all sub-regions of China except for southwest and eastern northwest China. Compared with wet compound and daytime HWs, wet nighttime HWs accompanied by more elevated relative humidity exhibit larger growth rates in frequency, occurring days, duration and affected areas. Additionally, most wet nighttime and compound HWs with the longest duration and/or the maximum intensity are found to occur after the mid-1990s, compared to fewer than half for wet daytime HWs. Our findings emphasize the prominent intensifying trends in wet nighttime HWs across China for the last 60 years, and suggest more efforts on exploring humid HWs.